2002
DOI: 10.1046/j.1523-1755.61.s80.20.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in hemodialysis patients: Is NADPH oxidase complex the culprit?

Abstract: Oxidative stress results from an imbalance between oxidant production, including reactive oxygen species (ROS), reactive nitrogen species (RNS), chlorinated compounds, and antioxidant defense mechanisms. Most reports prove that oxidative stress is present in ESRD patients. Several studies tend to accreditate the hypothesis by which oxidative stress is a strong co-factor for the development of complications related to long-term HD such as atherosclerosis, amyloidosis, malnutrition, anemia, and infection. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 34 publications
1
51
0
1
Order By: Relevance
“…Previous reports suggest that, in addition to proteinuria and hypertension, hyperlipidemia is the third important risk factor for CKD (43). Abnormal lipid metabolism and deposition are associated with microinflammation and oxidative stress (44). The current study demonstrated that PTH is positively correlated with the expression levels of serum TG, TC and LDL-C in patients with CKD, suggesting that hyperlipidemia is closely associated with SHPT.…”
Section: % CI ------------------------------Variablesupporting
confidence: 61%
“…Previous reports suggest that, in addition to proteinuria and hypertension, hyperlipidemia is the third important risk factor for CKD (43). Abnormal lipid metabolism and deposition are associated with microinflammation and oxidative stress (44). The current study demonstrated that PTH is positively correlated with the expression levels of serum TG, TC and LDL-C in patients with CKD, suggesting that hyperlipidemia is closely associated with SHPT.…”
Section: % CI ------------------------------Variablesupporting
confidence: 61%
“…40 Most reports prove that oxidative stress is present in end-stage renal disease patients, and oxidative stress would be a strong cofactor for the development of cardiovascular complications. 41 Considering the high prevalence of LVH in hemodialysis patients, our findings emphasize the need for clinical studies to determine the potential beneficial effects of MR blockade in patients with chronic renal failure.…”
Section: Perspectivesmentioning
confidence: 78%
“…The significantly enhanced priming of HD PMNL versus CKD not on RRT occurred despite blood withdrawal before HD session and may reflect accumulating nondialyzed uremic toxins as well as possible accumulating side effects of the extracorporeal treatment (23)(24)(25). From this and other studies (6), it seems that uremia per se is a major contributor to PMNL priming: PMNL priming was almost twofold higher in CKD patients who were not on RRT, compared with NC, whereas hemodialysis further increased the priming of PMNL by only 25%.…”
Section: Discussionmentioning
confidence: 99%